2021
DOI: 10.1074/jbc.ra120.015376
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an ancestral ADP-dependent kinase with fructose-6P reveals key residues for binding, catalysis, and ligand-induced conformational changes

Abstract: ADP-dependent kinases were first described in archaea, although their presence has also been reported in bacteria and eukaryotes (human and mouse). This enzyme family comprises three substrate specificities; specific phosphofructokinases (ADP-PFKs), specific glucokinases (ADP-GKs), and bifunctional enzymes (ADP-PFK/GK). Although many structures are available for members of this family, none exhibits fructose-6-phosphate (F6P) at the active site. Using an ancestral enzyme, we obtain the first structure of an AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…High protein stability is known to facilitate crystallization [27][28][29] , and it has been demonstrated that the structures of ancestral enzymes can be used as molecular scaffolds to unravel the structures and catalytic mechanisms of extant enzymes that are difficult to crystallize. [30][31][32][33][34][35] We previously used ancestral sequence reconstruction to obtain a stable ancestral enzyme Anc HLD-RLuc that was reconstructed from the catalytically distinct but structurally related HLDs and Renilla luciferase. 9 This ancestor enzyme turned out to have dual functions, with dehalogenase activity comparable to that of contemporary HLDs as well as promiscuous luciferase activity significantly lower than that of the stabilized RLuc8.…”
Section: Introductionmentioning
confidence: 99%
“…High protein stability is known to facilitate crystallization [27][28][29] , and it has been demonstrated that the structures of ancestral enzymes can be used as molecular scaffolds to unravel the structures and catalytic mechanisms of extant enzymes that are difficult to crystallize. [30][31][32][33][34][35] We previously used ancestral sequence reconstruction to obtain a stable ancestral enzyme Anc HLD-RLuc that was reconstructed from the catalytically distinct but structurally related HLDs and Renilla luciferase. 9 This ancestor enzyme turned out to have dual functions, with dehalogenase activity comparable to that of contemporary HLDs as well as promiscuous luciferase activity significantly lower than that of the stabilized RLuc8.…”
Section: Introductionmentioning
confidence: 99%